Five‐Fold Symmetric Pentaindolo‐ and Pentakis(benzoindolo)Corannulenes: Unique Structural Dynamics Derived from the Combination of Helical and Bowl Inversions. (23rd November 2021) - Kise, Koki; Ooi, Shota; Saito, Hayate; Yorimitsu, Hideki; Osuka, Atsuhiro; Tanaka, Takayuki
Abstract: Peripherally π‐extended corannulenes bearing quintuple azahelicene units, 10 and 11, were prepared and their dynamic behaviors were studied experimentally and theoretically. The fused corannulenes were synthesized from sym ‐pentabromocorannulene in three steps. X‐Ray diffraction analysis for 10 displayed a conformer possessing a P(M) bowl chirality and a PPMPM ( PMPMM ) helical chirality, which was found to be the most stable conformer(s). Variable‐temperature NMR measurements of 10 and 11 revealed that their structural isomers can be interconvertible in solution, depending on the steric congestion around the helical scaffolds. Automated search for conformers in the equilibrium and transition states by Artificial Force Induced Reaction (AFIR) method revealed their interconversion networks, including bowl‐inversion and helical‐inversion. This analysis indicated that the co‐existing corannulene and azahelicene moieties influence the conformational dynamics, which leads to mitigation of the activation energy barriers for isomerization. Abstract : Peripherally π‐extended corannulenes with five azahelicene units were prepared and their structural dynamics were studied experimentally and theoretically. This motif contains many conformational isomers owing to the helical and bowl chiralities. The interconversion networks were explored by using GRRM17 program, which revealed that the co‐existing corannulene and azahelicene moieties lower the activation energy barriers for some isomerization processes.